Effect of the derivatives of andrographolide on the morphology of Bacillus subtilis - Chantana Aromdee (2018)
Andrographis paniculata has been reported to have antiviral, antipyretic and anticancer activities. Andrographolide, an ent-labdane diterpene, is an active constituent in this plant. In this study, andrographolide (1) and its natural derivative 14-deoxy-11,12-didehydroandrographolide (2) and 5 other semisynthetic derivatives were tested for their activity against Grampositive and Gram-negative bacteria and Candida albicans. Only derivatives bearing a 14-acetyl group showed activity, and this activity was only against Gram-positive bacteria. 14-Acetylandrographolide showed the highest potency against Bacillus subtilis; the other 14-acetylandrographolides with additional substitution at the 3- and 19-hydroxyl groups showed lower activity against Gram-positive bacteria. The morphology of B. subtilis after being treated with 14-acetylandrographolide was investigated with TEM. This is the first report on 14-acetylandrographolide's quantified antibacterial activity, and the crucial functional group of this ent-labdane that plays an important role in perturbing the morphogenesis of B. subtilis leading to cell death. © 2011 The Pharmaceutical Society of Korea and Springer Netherlands.